2011
DOI: 10.1103/physrevb.83.165311
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the indium tin oxide/organic interface on open-circuit voltage, recombination, and cell degradation in organic small-molecule solar cells

Abstract: In this paper we investigate the performance and stability of small-molecule organic solar cells with respect to the indium tin oxide (ITO)/organic interface. Different zinc-phthalocyanine (ZnPc)/fullerene (C 60 ) cell architectures with and without ITO O 2 -plasma treatment are compared and tested with respect to their degradation behavior under illumination in inert atmosphere. Photoelectron spectroscopy (UPS and XPS) shows that the O 2 -plasma treatment increases the ITO work function from 4.3 eV up to 5.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 84 publications
2
48
0
Order By: Relevance
“…[56][57][58] In the context of organic solar cells, surface recombination is rarely discussed in much detail, and there are only few theoretical studies on its effects. 9,33,[59][60][61] However, there are extensive studies on cathode interlayers, [62][63][64] electrode work functions, [65][66][67][68] and hole transporting layers [69][70][71] and their effect on the device performance, including the open-circuit voltage. All of these studies implicitly support the theory that, at least in some organic solar cells, recombination at the contact affects the open-circuit voltage.…”
Section: Recombination At the Contactsmentioning
confidence: 99%
See 1 more Smart Citation
“…[56][57][58] In the context of organic solar cells, surface recombination is rarely discussed in much detail, and there are only few theoretical studies on its effects. 9,33,[59][60][61] However, there are extensive studies on cathode interlayers, [62][63][64] electrode work functions, [65][66][67][68] and hole transporting layers [69][70][71] and their effect on the device performance, including the open-circuit voltage. All of these studies implicitly support the theory that, at least in some organic solar cells, recombination at the contact affects the open-circuit voltage.…”
Section: Recombination At the Contactsmentioning
confidence: 99%
“…Due to the low dielectric constants, and in consequence due to the high exciton binding energies in molecular semiconductors, the situation is less clear in organic solar cells where geminate recombination of excitons or bound charge carriers can be a substantial loss mechanism. 1,2 However, recent studies [3][4][5][6][7][8][9][10][11][12][13] suggest that nongeminate recombination is limiting the efficiency of most well-performing bulk heterojunction solar cells. Experimentally, nongeminate recombination is often studied at the open circuit where, due to the lack of an external current flow, effects of series resistances and charge carrier transport are minimized.…”
Section: Introductionmentioning
confidence: 99%
“…This combination is typical for state-of-the-art organic BHJ solar cells which are not limited by the geminate recombination of CT-states, 63,64 but mainly by nongeminate recombination of free charge carriers. [23][24][25][26] Another proposed mechanism which could explain a weak temperature dependence was a dissociation process involving disorder-assisted tunneling jumps. 65 In contrast to this theory, a weak temperature dependence was found for both strongly and weakly disordered materials.…”
Section: Alternative Explanations For a Weak Temperature Dependencementioning
confidence: 99%
“…Recently, it was demonstrated that such nongeminate recombination losses, which occurred after exciton and CT-state dissociation, could explain the voltage dependence of the photocurrent of several state-of-the-art BHJ solar cells. [23][24][25][26][27] In such a case, the additional application of a field-dependent CT-state dissociation process has to result in overparametrization and ambiguous results.…”
Section: Introductionmentioning
confidence: 99%
“…The IPCE spectra of the IAPP device consist of five clearly distinguished peaks, three for zinc phthalocyanine (ZnPc) and two for the C 60 molecule. 3 The five peaks in the IPCE spectra of the IAPP sample correspond to the ZnPc at 340 nm, 630-640 nm and 680-700 nm, [11][12][13][14] and to the C 60 molecule at 380 nm and 460 nm. 19,20 The ZnPc peaks are in good correspondence with the absorption bands observed in the UV-Vis absorption spectra, called the B (or Soret) band around 300-400 nm in the UV region, and the Q band in the visible region between 400 and 800 nm.…”
Section: General Characterization Reference Devicesmentioning
confidence: 99%